Redox polymers for energy and nanomedicine - Casado, Nerea; Mecerreyes, David (RSC polymer chemistry series, 2021)
Redox Polymers for Energy and Nanomedicine highlights trends in the chemistry, characterization and application of polymers with redox properties.